Small cell lymphocytic lymphoma of eye annexes. Case presentation - Icilany Villares Álvarez; Julio Dámaso Fernández Águila; María de los A. García Dueñas; Alejandro Pérez Capote (Medisur)
Lymphomas are malignant diseases that originate in the immune system cells and are predominantly manifested by lymphadenopathy; sometimes the presentation is in extranodal places. The eye and its annexes may be affected by a heterogeneous group of primary lymphomas or, secondarily, by the extension of lymphomas originated in lymph nodes or other extranodal sites. The case of a patient who went to the consultation due to left palpebral ptosis is reported and physical examination showed bilateral involvement, with tumors in the lower right eye bulbar conjunctiva and in the left eye upper bulbar conjunctiva. A small B cell lymphocytic non-Hodgkin lymphoma was diagnosed by conjunctiva biopsy. The patient was considered a stage IIIAE of Ann Arbor and treated with six cycles of cyclophosphamide, vincristine, doxorubicin and prednisone, plus the Cuban monoclonal antibody anti-CD20 CIMABior®. The complete response was reached, state in which the disease remains so far.